Phytochemical and Nutritional Composition of Three Varieties of Cowpea (Vigna Unguiculata) Pre-Treated with Salicylic Acid Under Arsenic Stress - Ailenokhuoria, Bukola Victoria; Olaiya, Charles O (International Journal of Advances in Life Science and Technology, 2022)
Abiotic stress is one of the major factors limiting production and utilization of cowpea in developing nation of the world. Salicylic acid serve to promote and regulate plant growth. The work was design to examine the impacts of Salicylic acid on phytochemicals and nutritional composition of cowpea under arsenic stress. Three varieties of clean seeds of cowpea each were soaked in 0,75 and 150mg/L of salicylic acid for five hours. They were air-dried and sown in pots of soil containing 0, 250 and 500mg/L of sodium arsenate in a completely randomized design and were replicated thrice. The seeds were harvested at maturity and analyzed for phytochemical composition (total phenolic and flavonoid), Proximate composition (Crude protein, fat, ash, moisture, crude fibre and carbohydrate) and elemental composition (As, Ca, K, P, Mo, Mg and Zn). Data were analysed using ANOVA at α0.05. By comparing treatments with the control, crude protein, fat, phosphorus, calcium, magnesium and molybdenum were by increased by 2 folds among the three cultivars, total phenolic, flavonoid were increased by 4 and 2 folds in ART98-12, 5 and 3 folds in Ife brown and ITOK-568-18 in 250mg/L sodium arsenate-treated soil with SA (150mg/L). The result shows that 150mg/L of salicylic acid could be appropriate concentration to alleviate arsenic stress in cowpea .